The exclusivity of the administrative litigation process in the ordinary jurisdiction - Linares San Román, Juan José (2025)
This paper focuses on questioning the use of the claim for nullity of legal acts, based on Civil Code provisions, to request the annulment of administrative acts that are grounded in administrative law. Accordingly, it reaffirms the exclusivity of the administrative litigation process, within the ordinary jurisdiction, for filing claims seeking the annulment of administrative acts issued under public law norms.